Faktor-faktor yang mempengaruhi Perilaku Konsumen dalam Pengambilan Keputusan Memilih Hotel Syariah di Kota Medan - Larasati, Diah Larasati; Lubis, Fauzi Arif; Nasution, Juliana (Medan Resource Center, 2023)
The study investigates the development of Nasyiatul Aisyiyah in Medan City from 2016 to 2023, examining its progress and activities during this period. Utilizing historical research methods, including heuristics, verification, interpretation, and historiography, data were collected through observations, interviews, and documentation at the Muhammadiyah Regional Leadership (PDM) office in Medan City. Findings reveal significant advancements in Nasyiatul Aisyiyah's activities, albeit interrupted by the COVID-19 pandemic in 2020-2021, causing temporary halts. Despite challenges, Nasyiatul Aisyiyah persisted in aiding disaster-affected communities and launching new programs. Key initiatives implemented include parenting classes, disaster response, leadership training, international symposiums, and entrepreneurship workshops. Recommendations include further expansion and consistency in organizational values, enhanced member education, historical awareness, collaboration with other organizations, and community engagement to promote tolerance and inclusivity.